2019
DOI: 10.1088/1755-1315/382/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different seedling sources on growth and carrageenan yield of seaweed kappaphycus alvarezii cultivated in Marobo Waters, Muna Regency, Southeast (Se) Sulawesi, Indonesia

Abstract: The purpose of this study was to determine the effect of different seedling sources on growth and carrageenan yield of K. alvarezii. There were three various seedlings sources used in this study: local strain, tissue-cultured seedlings, and seedlings resulting from mass selection combined with tissue–cultured method called “prof’. This research was over three months (August-October 2018) in Marobo coastal waters, Bone District, Muna Regency SE Sulawesi using the longline method. The results showed that the dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The ratio of wet and dry weight is also higher compared to the research conducted by [14] for weights of 5g are 9.85:1. Furthermore, the ratios FW: DW resulted from this study were comparable to the previous study using tissue-cultured seedlings conducted in Marobo coastal area, SE Sulawesi, Indonesia (9.88:1) [13] and better than the ratio (11.36:1) of seaweed farming done for 30 days in India [23]. From this study, it was shown that 0.2 g L-1 of AMPEP was able to produce the ratio of FW: DW higher than other treatments.…”
Section: Ratio Of Fresh Weight (Fw) To Dry Weight (Dw)supporting
confidence: 86%
See 1 more Smart Citation
“…The ratio of wet and dry weight is also higher compared to the research conducted by [14] for weights of 5g are 9.85:1. Furthermore, the ratios FW: DW resulted from this study were comparable to the previous study using tissue-cultured seedlings conducted in Marobo coastal area, SE Sulawesi, Indonesia (9.88:1) [13] and better than the ratio (11.36:1) of seaweed farming done for 30 days in India [23]. From this study, it was shown that 0.2 g L-1 of AMPEP was able to produce the ratio of FW: DW higher than other treatments.…”
Section: Ratio Of Fresh Weight (Fw) To Dry Weight (Dw)supporting
confidence: 86%
“…The use of seedlings, named locally in North Buton, SE Sulawesi as 'Kulisusu', is one of the efforts to maintain the continuity of the quality of superior seedlings. The seedlings were originally produced by the grafting method [9,10,11,12] using prof [13,14,15] and local strain seedlings [11]. The prof seedlings were produced in 2 stages.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that epiphytes cover the surface of seaweed thalli, considerably reducing nutrient absorption ( Wakibia et al, 2006 ; Vairappan et al, 2007 ). According to Aeni et al (2019) , the combined effects of “ice–ice” disease and epiphyte development decreased the growth rate during K. alvarezii cultivation in southeast Sulawesi. Mulyaningrum et al (2019) compared healthy seaweed to infected seaweed and discovered that healthy seaweed had a higher carrageenan yield and gel strength than infected seaweed.…”
Section: Factors Affecting Carrageenan Yield and Productionmentioning
confidence: 99%
“…Low seedling quality is still one of the main obstacles to accelerate seaweed production in SE‐Sulawesi (Febriyanti et al., 2019; Rama et al., 2018). Using the same source of seaweed broodstock for seedlings is reported to contribute to lowering quality (Kumar et al., 2007), and therefore, micropropagated seaweed seed has been suggested to be used to boost production growth (Aeni et al., 2019). However, access to micropropagated seedlings is not readily available for local farmers in SE‐Sulawesi.…”
Section: Figurementioning
confidence: 99%